ESTUDO DO MANEJO TURÍSTICO NA GRUTA DE PINHEIRO SECO (PR):ESTRATÉGIAS PARA A GEOCONSERVAÇÃO DO PATRIMÔNIO ESPELEOLÓGICO - Massuqueto, Laís Luana (2013)
This work aims to study on the tourist management in Pinheiro Seco cave, located at the triple border among the municipalities of Castro, Dr. Ulysses and Cerro Azul, in state of Paraná. The caves that exist in this region are inserted in the Ribeira Valley Speleological Province and are developed in carbonate rocks belonging to the Itaiacoca Group (metadolomites and limestones). The Pinheiro Seco region demonstrates enormous potential of geotourism inasmuch as at this location there is one of the largest concentrations of carbonate caves in the state. The caves have great scientific value, justified by the diversity of features existing in such environment, which evidence genetic and evolutionary processes. The underground galleries stand out for greatness, being among the largest caves of the state, surpassing hundreds of meters of linear development. Furthermore, the variety of speleothems provides uniqueness and beauty to the caves. Currently, numerous caves are known in this region, which are the following presented in this work: Pinheiro Seco cave, Ribeirão Areial grotto, Catedral da Luz cave, Barreiro Imbuial cave and Monjolo cave. The local has other known caves, but not yet studied, as well as the place demonstrates a high probability of new speleological discoveries. Although this region is not yet a tourist hub, a few visits occur to the caves without any type of control, which may cause various risks to the speleological patrimony. Because this area is of great environmental importance,the combination of tourism with actions aiming minimal impact on geodiversity and biodiversity is essential, insofar as without a management of local tourism the natural site will be subject to various negative impacts resulting, consequently, in the degradation of this natural environment. Speleological researches, evolving several environmental mapping and surveying, were accomplished in order to identify and to characterize the natural and geotourism potential of the area subject of this essay. Beyond such surveying, a pilot study was developed in the region about the tourism carrying capacity and a map of the environmental weaknesses, in the Prinheiro Seco cave. The results may indicate actions to discipline the tourism use of natural resources in the region, seeking the geoconservation.